The workshop as a qualitative research approach: lessons learnt from a “critical thinking through writing” workshop - Ahmed, Sabreena; Mohd. Asraf, Ratnawati (2018)
The field of engineering has workshops incorporated in its stream of study as a space for the research on and innovation of a unique idea. However, in the field of education, workshops are limited to teacher education and professional development programmes. This paper discusses the possibility of using workshops as a qualitative research approach for Educational Research. To elaborate on this concept, the authors of the paper will inform the readers of the procedures they used in conducting a series of five workshops titled, “Critical thinking through writing Workshop” with 15 pre-university students in a public university in Malaysia in the fall semester of 2017. The findings show that workshops accommodate many characteristics of a qualitative study and can be considered as a research approach for the field of education.